2021
DOI: 10.4103/jid.jid_66_20
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Effects of Platelet Rich Fibrin

Abstract: Background: Other than releasing a bunch of growth factors and molecules, platelet concentrates (PCs), especially platelet-rich fibrin (PRF) has a potential role in antimicrobial activities. Aim: The aim of this present systematic review was to collect, evaluate, and compare the available evidence regarding the antimicrobial efficacy of all types of PRF and to highlight the underlying mechanisms along with their potential benefits based on their actions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
0
6
1
Order By: Relevance
“…The proportion of leukocytes in PRF decreases as centrifugation force increases (i-PRF: lower centrifugation force and high proportion of leukocytes, PRF: higher centrifugation force and thus lower proportion of leukocytes) [ 10 ]. This could explain why PRP and i-PRF have an antimicrobial effect in these previous studies, but PRF without previous ampicillin/sulbactam treatment demonstrated no such antimicrobial effect in our study [ 16 , 17 , 31 ].…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…The proportion of leukocytes in PRF decreases as centrifugation force increases (i-PRF: lower centrifugation force and high proportion of leukocytes, PRF: higher centrifugation force and thus lower proportion of leukocytes) [ 10 ]. This could explain why PRP and i-PRF have an antimicrobial effect in these previous studies, but PRF without previous ampicillin/sulbactam treatment demonstrated no such antimicrobial effect in our study [ 16 , 17 , 31 ].…”
Section: Discussioncontrasting
confidence: 50%
“…Even though the full effect mechanism is not yet fully understood, PRF has been demonstrated to possess antimicrobial features without additional work-up or preparation [15][16][17]. Studies have demonstrated that PRF has a bactericidal and growth-inhibiting effect against both biofilm-forming and periodontal microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…The use of low-speed centrifugation to obtain new types of PRF has previously been explored, having the advantage of producing a high number of cells such as leukocytes [ 8 ]. I-PRF (injectable PRF) is available in injectable form and coagulates a few minutes after injection [ 2 ] while A-PRF+ (advanced PRF) has shown superior properties when compared with standard PRF [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of low-speed centrifugation to obtain new types of PRF has previously been explored, having the advantage of producing a high number of cells such as leukocytes [ 8 ]. I-PRF (injectable PRF) is available in injectable form and coagulates a few minutes after injection [ 2 ] while A-PRF+ (advanced PRF) has shown superior properties when compared with standard PRF [ 8 ]. These two types of PRF have great potential for further clinical application because they are simple to prepare and use and do not require the addition of anticoagulants [ 6 ] and also have an enriched antimicrobial content [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation